Bioethical behaviors, attitudes and practices in professional Odontologists (Research, Society and Development, 2025)
The aim of this study was to examine the behaviors, attitudes and bioethical practices of dental professionals, to detect deficiencies in their training and in the application of ethical principles, and to propose strategies to strengthen ethics in the practice of the profession. The research was carried out by means of a narrative review of the literature, compiling information from databases such as Scielo, Google Scholar, PubMed and Dialnet. Articles published between 2002 and 2024 in English and Spanish were included, with search terms related to bioethics in dentistry. The results showed that, although dental students show a positive attitude toward biosafety, there are deficiencies in the teaching of this discipline, which affects their ability to face ethical dilemmas. In addition, the use of social networks in dentistry has generated problems related to informed consent and patient privacy. The importance of empathy and communication in the professional-patient relationship is also highlighted. The study concludes that it is urgent to strengthen training in bioethics, to integrate theoretical and practical teaching in academic programs and to establish clear regulations on dental advertising and the use of social networks, in order to guarantee ethical practice focused on the patient's wellbeing.